The Sabbath anthology - Millgram, Abraham Ezra, 1901-1998; Jewish Publication Society (Lincoln : University of Nebraska Press ; Philadelphia : Jewish Publication Society, 2018)
"The Sabbath Anthology delves into one of the earliest Jewish institutions--the holiday the prophet Isaiah characterized as "the day of delight"--Elucidating its history, laws, customs and traditions, religious and ethical insights, and observances in different eras throughout the world. A wealth of Jewish creativity past and present--"The Sabbath in Judeo-Hellenistic Literature" by Flavius Josephus and Philo Judaeus; Talmud and midrashim; medieval Jewish literature by Judah Halevi, Abraham ibn Ezra, and Moses Maimonides; modern Jewish literature by Solomon Schechter, Mordecai Kaplan, Sholom Asch, Hayyim Nahman Bialik, and Ahad Ha'am; short stories by S.Y. Agnon, I.L. Peretz, Meyer Levin, and Martin Buber; ceremonial and decorative art; musical compilations and programming--will yield delight for many Sabbaths to come"--Back cover.
Originally published with the title Sabbath : the day of delight (Philadelphia : Jewish Publication Society of America, 1944).
"First Nebraska paperback printing: 2018"--Title page verso.
Includes bibliographical references (pages 479-486).
Print version record.
Keywords: Sabbath; Sabbath; RELIGION / Judaism / General; Electronic books